Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00167-005-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Complications in knee arthroscopy

Abstract: All simple arthroscopic procedures during 1999 through 2001 performed at Baerum community hospital were retrospectively examined. Procedures were excluded when being part of more complex procedures. A total of 876 procedures performed on 785 patients were left for examination. Complications were registered from the patient record and all received a written questionnaire or phone call. The answer was obtained from 97.6%. The overall complications rate was low, giving total of 5.00%. A total of 0.68% of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 14 publications
3
32
0
1
Order By: Relevance
“…In Reigstad e Grimsgaard 18 study, a total of 876 procedures performed on 785 patients were left for examination. The overall complications rate was low, giving total of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…In Reigstad e Grimsgaard 18 study, a total of 876 procedures performed on 785 patients were left for examination. The overall complications rate was low, giving total of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…However, each portal has the potential for drainage, stitch abscess, fibrosis, and tenderness that can contribute to postoperative morbidity. [3][4][5][6][7] Portal fibrosis peaks at 6 months postoperatively and resolves in only 50% of cases at 1 year postoperatively, as determined by magnetic resonance imaging. 7 A previous study showed that 2-portal knee arthroscopy improved recovery of knee strength and time to return to work by more than half compared with a 3-portal technique.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45]. Although the complications of arthroscopy are infrequent, their prevalence appears to be increasing, or at least there is improved recognition and reporting of complications.…”
Section: Complicationsmentioning
confidence: 99%